2006
DOI: 10.1007/s00381-006-0091-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of cerebral salt wasting (CSW) in children: the role of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP)

Abstract: Natriuresis and polyuria are the main diagnostic criteria for CSW. The fluid balance in CSW is negative, in contrast to a positive fluid balance in SIADH. The length of the disease is self-limited and generally ceases within 2 weeks, while Na+, K+, and fluid turnover should be monitored carefully. Only a minority of our children showed elevated ANP/BNP levels. A dose/effect relationship for natriuretic peptide levels and increased Na+ turnover could not be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 26 publications
3
35
1
1
Order By: Relevance
“…The occurrence of CSWS in children is uncommon 6 – 8. It has been reported in association with a variety of CNS pathologies (table 1) and may be triggered by stressful stimuli such as surgical procedures, general anaesthesia, or sepsis 9. To our knowledge, the patient described here is the first reported case of CSWS following a spinal cord injury.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The occurrence of CSWS in children is uncommon 6 – 8. It has been reported in association with a variety of CNS pathologies (table 1) and may be triggered by stressful stimuli such as surgical procedures, general anaesthesia, or sepsis 9. To our knowledge, the patient described here is the first reported case of CSWS following a spinal cord injury.…”
Section: Discussionmentioning
confidence: 73%
“…Kappy et al suggested that CSWS is caused by inappropriate secretion of ANH 6. However, ANH increase is not always seen in CSWS,9 and its presence does not confirm the diagnosis of CSWS as it may also be raised in SIADH 4. Conversely, an elevated serum ADH does not exclude a diagnosis of CSWS, as it may be raised physiologically in response to hypovolumeia 12.…”
Section: Discussionmentioning
confidence: 97%
“…La hiponatremia revierte con volumen y sal 12 . La poliuria es frecuente 9,13 . Desgraciadamente los hallazgos de laboratorio en SIADH y EPS son iguales y la depleción de volumen no es fácil de reconocer clínicamente, dificultando su diferenciación con SIADH.…”
Section: Discussionunclassified
“…ANH can lead to complications such as seizures or exacerbation of brain edema and raised intracranial pressure. The mechanisms behind the phenomenon of ANH remain controversial [1][2][3], with some authors arguing it is largely due to syndrome of inappropriate secretion of antidiuretic hormone (SIADH) [4] and others arguing that the underlying mechanism is cerebral salt wasting (CSW) [5][6][7][8]. Because these two very different pathophysiological explanations can currently be distinguished in clinical practice only by assessment of volume status and fluid balance, the controversy about the underlying mechanism of ANH is likely to persist for the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%